Aktualisasi Nalar Zari’ah dalam Mengantisipasi Kejahatan melalui Financial Technology - arif, firman muhammad (Institut Agama Islam Negeri (IAIN) Bone, 2019)
Technology-based financial services are an age-old innovation that simplifies processes and makes it easy. The new development is in line with the emergence of new crimes which actually disturb society. The formula of Islamic law sourced from revelation both textually, meaningfully and spirit is used as a media to mitigate the rampant damage. Normalization of bad conditions can only be realized by ensuring the actualization of zari'ah reason which is loaded with optimizing benefits or maximizing benefits. This paper intends to make zar'iah reasoning as a scalpel and initially normative analysis becomes actual in the public sphere because with the existence of zari'ah reasoning so that several cases including the rise of illegal fintechs are dissected, analyzed, reconstructed and minimized so that conditions can be conducive or crime can be minimized. The ideality of zari'ah in the formula for extracting Islamic law which has been formulated by the salaf cleric is considered still relevant to the times that are always laden with dynamics and change. Reason zari'ah with its two variants, sadd (closing, blocking) and fathu al zariah (opening the media, be careful) in this paper gives an assessment that sadd al zari'ah is prioritized over fathu al zari'ah. New developments always lead to new crime so that other supporting media are needed to eliminate or minimize crime from the rise of illegal finteches which ensnare victims and boost unilateral profits rather than encouraging community independence.Jasa keuangan berbasis teknologi adalah inovasi zaman yang menyederhanakan proses dan memudahkan. Perkembangan yang baru seiring dengan munculnya kejahatan baru yang justru meresahkan masyarakat. Formula hukum Islam yang bersumber dari wahyu baik secara tekstual, maknawiyah dan spirit dijadikan media untuk memitigasi maraknya kerusakan. Normalisasi keadaan buruk hanya bisa direalisasikan dengan memasifkan aktualisasi nalar zari’ah yang sarat dengan mengoptimalkan maslahat atau memaksimalkan maslahat. Tulisan ini bermaksud menjadikan nalar zar’iah sebagai pisau bedah dan analisis yang awalnya normatif menjadi aktual di ranah publik sebab dengan adanya nalar zari’ah inilah sehingga beberapa perkara termasuk maraknya fintech ilegal dibedah, ditelaah, direkonstruksi dan diminimalisir supaya keadaan menjadi kondusif atau kejahatan dapat terminimalisir. Idealitas nalar zari’ah dalam formula penggalian hukum Islam yang telah dirumuskan ulama salaf dinilai masih relevan dengan perkembangan zaman yang selalu sarat dengan dinamika dan perubahan. Nalar zari’ah dengan dua variannya, sadd (menutup, menghalangi) dan fathu al zariah (membuka media, wasilah) dalam tulisan ini memberikan penilaian bahwa sadd al zari’ah lebih diprioritaskan daripada fathu al zari’ah. Perkembangan baru selalu memunculkan aksi kejahatan baru sehingga diperlukan media pendukung lainnya untuk menghilangkan atau meminimalisir tindakan kejahatan dari maraknya fintech ilegal yang menjerat banyaknya korban dan mendongkrak keuntungan sepihak daripada mendorong kemandirian masyarakat.